Psychiatric disorders in individuals born very preterm / very low-birth weight: An individual participant data (IPD) meta-analysis. (December 2021) - Anderson, Peter J; de Miranda, Debora Marques; Albuquerque, Maicon Rodrigues; Indredavik, Marit Sæbø; Evensen, Kari Anne I.; Van Lieshout, Ryan; Saigal, Saroj; Taylor, H. Gerry; Raikkonen, Katri; Kajantie, Eero; Marlow, Neil; Johnson, Samantha; et al.
Abstract: Background: Data on psychiatric disorders in survivors born very preterm (VP; <32 weeks) or very low birthweight (VLBW; <1500 g) are sparse. We compared rates of psychiatric diagnoses between VP/VLBW and term-born, normal birthweight (term/NBW) control participants. Methods: This individual participant data (IPD) meta-analysis pooled data from eligible groups in the Adults born Preterm International Collaboration (APIC). Inclusion criteria included: 1) VP/VLBW group (birth weight <1500 g and/or gestational age <32 weeks), 2) normal birth weight/term-born control group (birth weight >2499 g and/or gestational age ≥37 weeks), and 3) structured measure of psychiatric diagnoses using DSM or ICD criteria. Diagnoses of interest were Attention Deficit Hyperactivity Disorder (ADHD), Autism Spectrum Disorder (ASD), Anxiety Disorder, Mood Disorder, Disruptive Behaviour Disorder (DBD), Eating Disorder, and Psychotic Disorder. A systematic search for eligible studies was conducted (PROSPERO Registration Number 47555). Findings: Data were obtained from 10 studies (1385 VP/VLBW participants, 1780 controls), using a range of instruments and approaches to assigning diagnoses. Those born VP/VLBW had ten times higher odds of meeting criteria for ASD (odds ratio [OR] 10·6, 95% confidence interval [CI] 2·50, 44·7), five times higher odds of meeting criteria for ADHD (OR 5·42, 95% CI 3·10, 9·46), twice the odds of meeting criteria for Anxiety Disorder (OR 1·91, 95% CI 1·36, 2·69), and 1·5 times the odds of meeting criteria for Mood Disorder (OR 1·51, 95% CI 1·08, 2·12) than controls. This pattern of findings was consistent within age (<18 years vs. ≥18 years) and sex subgroups. Interpretation: Our data suggests that individuals born VP/VLBW might have higher odds of meeting criteria for certain psychiatric disorders through childhood and into adulthood than term/NBW controls. Further research is needed to corroborate our results and identify factors associated with psychiatric disorders in individuals born VP/VLBW. Funding: Australia's National Health & Medical Research Council; CAPES (Coordenação de Aperfeiçoamento de Pessoal deNível Superior) - International Cooperation General Program; Canadian Institutes of Health Research Team Grant; National Council for Scientific and Technological Development (CNPq); Academy of Finland; Sigrid Juselius Foundation; Signe and Ane Gyllenberg Foundation; European Union's Horizon 2020 research and innovation programme: Project RECAP-Preterm; European Commission Dynamics of Inequality Across the Life-course: structures and processes (DIAL); Neurologic Foundation of New Zealand; MRC programme grant; Health Research Council of New Zealand; National Institutes of Health, USA; The Research Council of Norway; Joint Research Committee between St. Olavs Hospital and Faculty of Medicine and Health Sciences, Norwegian University of Science and Technology (NTNU); Liaison Committee between Central Norway Regional Health Authority and NTNU.